A comparison of high b-value vs standard b-value diffusion-weighted magnetic resonance imaging at 3.0 T for medulloblastomas - Han, Chengkun (Br J Radiol, 2015)
OBJECTIVE: To investigate the utility of diffusion-weighted (DW) MRI using high b-value vs standard b-value for patients with medulloblastoma (MB). Minimum apparent diffusion coefficient (ADC(MIN)) values were also compared with tumour cellularity. METHODS: High and standard b-value DW images were obtained for 17 patients with MB. The number and location of the lesions, signal intensities (SIs), signal-to-noise ratios (SNRs), contrast-to-noise ratios, contrast ratios (CRs) and ADCs of the lesions were compared. Tumour cellularity was also measured and compared with ADC(MIN) values. RESULTS: All 20 lesions were hyperintense on the DW MR images with high and standard b-values. Four additional lesions were revealed on high b-value, and all 24 lesions were more conspicuous at high b-value. SI, SNR and ADC values for the lesions were lower in the high b-value images than in the standard b-value images. The ADC(MIN) value at b = 3000 s mm(−2) was more significantly associated with tumour cellularity than that at b = 1000 s mm(−2). CR values were significantly higher in the high b-value images than in the standard b-value images. CONCLUSION: DW imaging using high b-value may be beneficial for detecting additional, less prominent lesions and may improve the contrast between MB lesions and normal tissue. A stronger inverse correlation with tumour cellularity was identified using the ADC(MIN) values at high b-value. ADVANCES IN KNOWLEDGE: This study demonstrates the superiority of high b-value DW imaging compared with standard b-value imaging for the detection of MB lesions, especially those with subtle foci.